Double Vessel Coronary Angioplasty in a Patient with Anomalous Single Coronary Artery Arising from the Right Cusp and Premature Atherosclerotic Coronary Artery Disease: A Case Report and Review of the Literature - Varun Kumar; Shalini Gupta; Krishna Prasad (Case Reports in Cardiology)
We report a rare case of a 39-year-old male who presented with acute inferior wall myocardial infarction (IWMI). Coronary angiography revealed an anomalous single coronary artery arising from the right coronary cusp. Premature atherosclerotic coronary artery disease (CAD) with critical stenosis in the mid right coronary artery (RCA), proximal posterior left ventricular (PLV) artery, and distal left circumflex (LCX) artery was detected during angiography. The patient managed successfully by percutaneous coronary interventions (PCI) with drug-eluting stents (DESs) by radial approach.